Santripreneur: Digital Transformation in Halal Start-Up Management for Islamic Boarding School Students [Santripreneur: Transformasi Digital Dalam Manajemen Start-Up Halal Bagi Santri] - 'Ilmi, Zujajatul; Novitasari, Dwi; Muttaqi'in, Ninnasi; Meutia, Nur Shabrina; Putra, Riyan Sisiawan (UKInstitute, 2025)
Abstract. Insan Cendekia Mandiri Boarding School (ICMBS) Sidoarjo is a boarding educational institution that provides free education for outstanding orphaned children at the junior and senior high school levels from various regions in Indonesia. This community service activity was carried out under the theme